Optimizing the Use of Social Media as a Brand Destination-based Promotional Media for Glagah Wangi Istambul Beach in Demak - Cahyo Wulandari (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2021)
Glagah Wangi Istambul Beach is one of the new natural tourist destinations in the Demak Regency, experiencing rapid development. This beach's management is carried out directly by Tambakbulusan Village people through the Village-Owned Enterprises (Badan Usaha Milik Desa, BUMDes). Community-based tourism adopts as a village development strategy to establish independence and improve community well-being. Promotion is an essential part of the development of a tourist attraction, including Glagah Wangi Istambul Beach. Advertising through social media has become a good strategy in the digital era because the internet has reached the villages nowadays. However, through social media, promotional efforts have not been carried out optimally by Glagah Wangi Istambul Beach's tourism manager. The COVID-19 pandemic situation led to the KKN PPM or Student Community Services-Community Empowerment UGM online, which was previously done by going into the field and interacting directly with residents. This condition creates limitations in determining what programs we can implement. The KKN PPM UGM JT 314 team (2020) focuses on solving the lack of efforts to promote tourism objects in Glagah Wangi Istambul Beach through branding destinations to take advantage of social media. Team did the data collection through observation, literature study, and online interviews. An online survey was also conducted in a google form questionnaire for visitors to evaluate the Sapta Pesona (Seven Enchantments) implementation. The activities carried out to promote the beach in this program are the procurement of some competitions such as creating creative photos, Tambakbulusan Village profiles infographics, health protocol guide during the pandemic, website management, and tourist promotion destinations through online media. The result of service activities shows increased public awareness of social media's importance to promote tourism objects.